PENGARUH PERTUMBUHAN EKONOMI, TINGKAT PENDIDIKAN, DAN PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI KABUPATEN BANGKALAN - Muniroh, Lum Atul; Septiana, Aldila; Arief, R. Zaiful (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023, 2023)
This research was conducted to determine whether there is a partial and simultaneous relationship between economic growth, level of education and reactions to poverty in Bangkalan Regency. The results of this study note that after testing all variables have the same results where the economic growth variable, the education level variable, the response variable have no effect on poverty either in a simulation or in part. This reserch is approach with 5 responden. In this study, the data used is published data from the central statistic agency (BPS) in the form of economic growth, education level, unemployment and poverty rate in bangkalan regency.